Deconstruction and Religion: Exploring Derrida’s View on Religion: Dekonstruksi dan Agama: Menelisik Pandangan Derrida tentang Agama - Patrick, Arokiaraj Joseph (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2023)
In today’s postmodern world, the idea of having absolute theories or absolute truth is rejected. This has also created a problem of how to explain religion, which is an important part of human nature. Most postmodern philosophers think there is an element of spiritual desire in each human being which is seeking the Wholly Other for its fulfilment. Hence in their own way, they have tried to explain this mystical desire in humans. Derrida has been seen as a major contributor towards the philosophy of religion in recent times. Through his project of deconstruction, he has tried to show how deconstruction is deeply religious. Deconstruction of religion is not the destruction of religion but its reinvention. The method of deconstructionism tends to teach us to move beyond the boundaries of philosophical concepts. It creates an attitude of openness towards the Wholly Other that may come or not come but we need to live as if the Other has come. Derrida’s religion portrays well the postmodernist faith. Based on his Jewish background, he finds religion to be like deconstruction, which is waiting for the Really Real or the absolute Truth. He has brought out the mystical aspect of religion through deconstruction. Abstrak Di era postmodern, gagasan mengenai teori yang bersifat mutlak atau ide tentang kebenaran absolut tidak bisa diterima lagi. Hal ini menimbulkan persoalan: bagaimana menjelaskan agama yang memiliki perang penting dalam hidup manusia. Sebagian besar pemikir postmodern sebetulnya percaya bahwa ada kerinduan spiritual dalam tiap manusia yang mencari pemenuhannya dalam Diri Yang Sepenuhnya Lain (Wholly Other). Dengan cara mereka yang khas, mereka berusaha menjelaskan kerinduan mistik ini. Derrida merupakan salah satu pemikir postmodern yang berkontribusi pada Filsafat Ketuhanan kontemporer. Sejatinya proyek dekonstruksi yang dikembangkannya bersifat religius. Dekonstruksi agama bukanlah destruksi agama, melainkan penemuan kembali agama. Dekonstruksi adalah suatu metode untuk melampaui batas-batas konsep-konsep filosofis. Metode ini membuat manusia bersikap terbuka pada Diri Yang Sepenuhnya Lain, hal mana mungkin hadir atau tidak hadir namun memaksa kita menghayatinya seolah-olah telah hadir. Agama yang digambarkan Derrida ini merupakan potret iman postmodern. Bertolak dari latar belakang Yahudi, Derrida mengalami agama sebagai sebuah dekonstruksi, yang masih menunggu Apa Yang Sepenuhnya Nyata atau Kebenaran Absolut. Melalui dekonstruksi ia menyingkapkan aspek mistik agama. Kata-kata Kunci: dekonstruksi, Derrida, postmodernisme, iman, postmodern, agama